CityGML-based model for the recovery and management of built cultural heritage: a systematic review towards digitalized processes - Margherita Lasorella; Elena Cantatore (City, Territory and Architecture)
Abstract Over the last few decades, digital and parametric modelling of buildings and cities on a large scale has demonstrated a growing trend. Moreover, these applications have underscored the need for a higher level of organization in managing built Cultural Heritage, which traditionally relies on well-structured methods and multidisciplinary skills. In light of this, the paper presents the results of a systematic review of the CityGML standard for designing architectural and built Cultural Heritage for recovery and maintenance. Specifically, the review focuses on CityGML-based models and their multi-dimensional extensibility (from the buildings to the territorial scale), considering different scales (based on geographical and spatial dimensions of built Cultural Heritage), fields of application (maintenance, conservation, risk assessment), ontological rules (whether new or pre-existing), and the integration of Decision Support Systems (e.g., automation of processes in assessing architectures and their systems, as well as the required interventions). Thanks to the use of the PRISMA-S checklist, the review involves a first sample of 196 scientific works, selecting 57 for the detailed analysis. The process has highlighted the extensive use of digital CityGML-based models for all scales of the built Cultural Heritage. However, the main objectives are cataloguing and systematizing technical knowledge at the building scale to solve the requirement of standardized information. Due to that, the use of ontologies integrated with standards supports the aim by varying thematic qualities and details of the contents, coherently with the fields of application. This extensibility is also reflected in the application of external rules providing structured logic for Cultural Heritage management and automatic or semi-automatic support for policymakers’ decisions in collaborative and multi-disciplinary digital environments. In this framework, experiences are finally discussed in terms of opportunities to use CityGML-based models to support traditional methods for the built Cultural Heritage into digital tools and platforms, exploring possible scenarios of future application fields.